Emerging role of ZBTB7A as an oncogenic driver and transcriptional repressor. (28th July 2020) - Gupta, Sanjay; Singh, Atul Kumar; Prajapati, Kumari Sunita; Kushwaha, Prem Prakash; Shuaib, Mohd; Kumar, Shashank
Abstract: ZBTB7A is a member of the POK family of transcription factors that possesses a POZ-domain at the N-terminus and Krüppel-like zinc-finger at the c-terminus. ZBTB7A was initially isolated as a protein that binds to the inducer of the short transcript of HIV-1 virus TAT gene promoter. The protein forms a homodimer through protein-protein interaction via the N-terminus POZ-domains. ZBTB7A typically binds to the DNA elements through its zinc-finger domains and represses transcription both by modification of the chromatin organization and through the direct recruitment of transcription factors to gene regulatory regions. ZBTB7A is involved in several fundamental biological processes including cell proliferation, differentiation, and development. It also participates in hematopoiesis, adipogenesis, chondrogenesis, cellular metabolism and alternative splicing of BCLXL, DNA repair, development of oligodendrocytes, osteoclast and unfolded protein response. Aberrant ZBTB7A expression promotes oncogenic transformation and tumor progression, but also maintains a tumor suppressive role depending on the type and genetic context of cancer. In this comprehensive review we provide information about the structure, function, targets, and regulators of ZBTB7A and its role as an oncogenic driver and transcriptional repressor in various human diseases. Highlights: ZBTB7A is a member of POZ domain containing transcription factors family. ZBTB7A repress transcription by recruiting co-repressor complexes at DNA. ZBTB7A overexpression is positively associated with various cancers. Oncogenic role of ZBTB7A is cancer type dependent. ZBTB7A plays an important role in various cellular and developmental processes.